Gendered Pathways of Labour Integration: Migrant Workers in Urban Economic Zones in Ethiopia - Adedeji Daniel Gbadebo (Indonesian Academy of Social and Religious Research (IASRR), 2026)
This study investigates the labour market integration of migrant workers in Ethiopia’s urban economic zones, with a focus on how gender shapes employment outcomes, occupational mobility, and access to social protection. Drawing on neoclassical and structural migration theories, gendered migration frameworks, and labour market segmentation literature, the study examines the intersections of migration status, gender, and urban economic structures. Using evidence from industrial parks, special economic zones, and informal urban markets, the research highlights patterns of formal and informal employment, wage disparities, skill utilization, and occupational segregation. It further explores institutional, social, and structural barriers, including legal restrictions, discrimination, care responsibilities, housing precarity, and vulnerability to exploitation, demonstrating how these disproportionately affect women and other marginalized groups. The study concludes by proposing gender-responsive policies, inclusive urban planning, and skills recognition frameworks to enhance equitable labour integration.